My 'Highlanders' Family - Soubakeavathi, Rethinasamy (UNIMAS Publisher, 2022)
On the 1"t of -October 2000, leaving behind my barely lvTone-year-old baby in the capable hands of Ashley, i headed to Bario with the eBario team. The team boarded a plane from Kuching to Miri and rater a 12-seater twin otter flight from Miri to Bario. The weather was rough and thus it was indeed a bumpy ride all the way from Miri to Bario. Iwas feeling dizzy andnauseated. When we finally landed, I clumsily got out of the plane and headed towards the tiny Bario Airport - it was hardly an airport in the e1-es of arr urban girl. A group of people inch,ding Cikgu Lucy Buian greeted us at the airpori. Their .-i1", uid E arm welcome made my dizziness and nausea evaporate urto the cool fresh air of Bario!